Shallow Lakes in a Changing World 2007
DOI: 10.1007/978-1-4020-6399-2_8
|View full text |Cite
|
Sign up to set email alerts
|

Searching for allelopathic effects of submerged macrophytes on phytoplankton—state of the art and open questions

Abstract: Allelopathy, here defined as biochemical interactions between aquatic primary producers, has always been intriguing as a process explaining the dominance of certain plant or algal species over others. Negative chemical interference has been invoked as one of the steering mechanisms behind mutual dominance of either submerged macrophytes or phytoplankton in shallow eutrophic lakes. Yet, despite much effort, convincing evidence for allelopathic interactions in situ is still missing. Also, laboratory approaches o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 61 publications
1
41
0
1
Order By: Relevance
“…Biological method is one of the most innovative technologies for environmental restoration in recent years, which has become a hotspot in the field of environment research [17][18][19][20][21][22]. Studies have shown that many kinds of aquatic plants have the ability to resist and control eutrophication, such as reed, Ceratophyllum demersum, Ruppia [4,[23][24][25]. Due to the advantages of high efficiency, low cost, and no secondary pollution, the method of algae control by plant allelopathy is of great significance for preventing and repairing water bodies from eutrophication [24,[26][27][28], and maintaining water stability after restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Biological method is one of the most innovative technologies for environmental restoration in recent years, which has become a hotspot in the field of environment research [17][18][19][20][21][22]. Studies have shown that many kinds of aquatic plants have the ability to resist and control eutrophication, such as reed, Ceratophyllum demersum, Ruppia [4,[23][24][25]. Due to the advantages of high efficiency, low cost, and no secondary pollution, the method of algae control by plant allelopathy is of great significance for preventing and repairing water bodies from eutrophication [24,[26][27][28], and maintaining water stability after restoration.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, we expect that the development of diverse types of macrophytes (submerged and free-floating) will create more physically complex habitats in aquatic ecosystems and support high zooplankton biodiversity. In contrast, extensive cover by free-floating macrophytes is expected to reduce underwater biomass as a result of shading effects (Gross et al, 2007). In other words, excessive growth of free-floating macrophytes would be expected to induce a relatively simple habitat structure, leading to a smaller, less diverse assemblage of zooplankton.…”
Section: Introductionmentioning
confidence: 99%
“…In the water bodies where dominant macrophytes are observed, usually there is a strong competition for the resources of nutrients, light, and allelopathy observe (van Donk et al 1993;Scheffer and Jeppesen 1998;Gross et al 2007). Ma is an example of such reservoirs.…”
Section: Macrophytesmentioning
confidence: 99%
“…Oxbow lakes in this phase may even be compared to shallow macrophyte lakes (Scheffer and Jeppesen 1998;Scheffer and van Nes 2007). In oxbow lakes, competition occurs between phytoplankton and submerged vegetation, and accompanying vascular vegetation mats of filamentous algae-metaphyton (Gross et al 2007;Irfanullah and Moss 2005).…”
Section: Introductionmentioning
confidence: 99%